Substance Use Among Older People Living With HIV: Challenges for Health Care Providers - Deren, Sherry; Cortes, Tara; Dickson, Victoria Vaughan; Guilamo-Ramos, Vincent; Han, Benjamin H.; Karpiak, Stephen; Naegle, Madeline; Ompad, Danielle C.; Wu, Bei (Frontiers in Public Health, 2019)
Older people living with HIV (OPLWH) have higher rates of substance use (tobacco, alcohol and other drugs) than their HIV-negative peers. Addressing health care needs of OPLWH who use substances is more challenging than for those who do not: they are highly impacted by comorbid conditions, substance use can interact with other medications (including antiretroviral therapy-ART) and reduce their effectiveness, and substance use has been associated with reduced adherence to ART and increased risky behaviors (including sexual risks). People who use substances also suffer disparities along the HIV continuum of care, resulting in lower viral suppression rates and poorer health outcomes. They are especially impacted by stigma and stress, which have implications for HIV treatment and care. Recommendations for health care providers working with OPLWH who use substances include: 1) the need to screen and refer for multiple associated conditions, and 2) training/continuing education to enhance care management and maximize health outcomes.